Long-term and short-term dynamic relationships on the country Stock Market Index due to the impact of explosion of Ammonium Nitrate (NH4NO3) in Beirut, Lebanon: An event study analysis on the Stock Market Index of countries in The Middle East and the country Stock Market Index in Indonesia - Adristi, Fikri Irfan; Moin, Abdul (Jurnal Siasat Bisnis, 2023)
Objectives ─ This research aims to examine the long-term and short-term dynamic relationships of the major stock market indices in Lebanon (BLSI), Israel (TA35), Jordan (AMGNRLX), Saudi Arabia (TASI), and Indonesia (IHSG) due to the impact of the ammonium nitrate explosion. (NH4NO3) in Beirut, Lebanon. Method ─ This research used samples after the explosion of ammonium nitrate (NH4NO3) in Beirut, Lebanon, from 10 August 2020 to 17 December 2020. Long-term and short-term dynamic relationships due to the impact of the ammonium nitrate (NH4NO3) explosion in Beirut, Lebanon were tested using the Johansen Cointegration Test and Granger Causality Test methods. Findings ─ The results show that: (1) There is a cointegration relationship in the return of the country stock market index in Lebanon (BLSI), Israel (TA35), Jordan (AMGNRLX), Saudi Arabia (TASI), and Indonesia (IHSG) after the explosion; (2) there is no bi-directional causality relationship or unidirectional relationship between benchmark variables, that is Return BLOM Stock Index (BLSI) with the Return TA-35 (TA35), Return Amman SE General (AMGNRLX), Return Tadawul All Share Index (TASI), and Return Indeks Harga Saham Gabungan (IHSG) variable after the explosion event. Originality ─ This paper presents a novelty with a study of events that link human events and capital market indices.